To solve this problem, we need to use the consumer utility maximizing rule:
(MU A / P A) = (MU B / P B)
We are given that the marginal utility of good A is 3 times the marginal utility of good B, and the price of good A is $4.50.
Let's assume that the marginal utility of good B is MU B.
Therefore, the marginal utility of good A is 3MU B.
We also know that the price of good A is $4.50.
Plugging these values into the consumer utility maximizing rule, we get:
(3MU B / $4.50) = (MU B / PB)
Cross-multiplying, we get:
(3MU B) * (PB) = (MU B) * ($4.50)
Simplifying, we get:
3MU B * PB = MU B * $4.50
Dividing both sides by MU B, we get:
3PB = $4.50
Dividing both sides by 3, we get:
PB = $1.50
Therefore, the price of good B is $1.50.
Finally, to find the price of good A, we can plug the price of good B into the consumer utility maximizing rule:
(MU A / $4.50) = (MU B / $1.50)
Since we know that MU A is 3 times MU B, we can substitute 3MU B for MU A:
(3MU B / $4.50) = (MU B / $1.50)
Cross-multiplying, we get:
(3MU B) * ($1.50) = (MU B) * ($4.50)
Simplifying, we get:
4.5MU B = 1.5MU B
Dividing both sides by MU B, we get:
4.5 = 1.5
Therefore, the equation does not hold true and there may be an error in the original question or provided answer.
Please double-check the information and equations given to ensure accuracy in solving the problem.
the marginal utility of good A is 3 imes the marginal utility of good B, and the price of good A is $4.50
Use consumer utility mazimizing rule ( MU A / P A) =(MUB/ PB) to solve. The answer is $6.75.
1 answer